Coming Back to Edmonton: Competing with Former Employers and Colleagues - Grohsjean, Thorsten; Kober, Pascal; Zucchini, Leon (Academy of Management Journal, 2016)
Drawing on human and social capital theory, research on employee mobility has discussed the benefits and drawbacks of hiring employees from rival firms. To explain the performance implications of employee mobility, the literature has focused on what moving individuals can do, but has ignored what they are willing to do. However, to fully understand what individuals will actually do at the new firm, we need to understand both. We argue that what individuals are willing to do depends on their collective and relational identity. When competing against a former employer, individuals experience a conflict in their collective identity as they identify with both organizations but can only increase the welfare of one. To reduce this conflict, individuals strengthen their identification with the new organization and deidentify with the former by competing harder against the former organization. At the relational level, individuals can still identify with their ex-colleagues without harming the welfare of the new organization by competing harder with non-former colleagues but behaving less competitively toward former colleagues. We analyze data from the National Hockey League and find strong support for our hypotheses.